2013
DOI: 10.1111/iep.12041
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of the normal Clara cell phenotype after chronic allergic inflammation

Abstract: Bronchiolar Clara cells play a critical role in lung homoeostasis. The main goal of this study was to evaluate the effects of chronic allergy on these cells and the efficacy of budesonide (BUD) and montelukast (MK) in restoring their typical phenotypes after ovalbumin-induced chronic allergy in mice. Chronic allergy induced extensive bronchiolar Alcian blue-periodic acid-Schiff (AB/PAS)-positive metaplasia. In addition, cells accumulated numerous big electron-lucent granules negative for Clara cell main secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
(78 reference statements)
1
15
0
Order By: Relevance
“…Previous findings of our group revealed an alteration of the CC defensive mechanisms, including the CCSP and SP-D content, along with the mucus metaplasia establishment. 18,19 In this study, LPS exposition prior to allergen challenge resulted in a meaningful reduction in the mucus hypersecretion, which correlated with decreased EGFR expression. Indeed, CC achieved a better preservation of their typical phenotype, including CCSP and SP-D content together with the increase in TLR4 and TNFa expression.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Previous findings of our group revealed an alteration of the CC defensive mechanisms, including the CCSP and SP-D content, along with the mucus metaplasia establishment. 18,19 In this study, LPS exposition prior to allergen challenge resulted in a meaningful reduction in the mucus hypersecretion, which correlated with decreased EGFR expression. Indeed, CC achieved a better preservation of their typical phenotype, including CCSP and SP-D content together with the increase in TLR4 and TNFa expression.…”
Section: Discussionmentioning
confidence: 53%
“…19 Briefly, after being blocked, the sections were Diaminobenzidine (DAB, Sigma-Aldrich), which was used as a chromogen substrate, and the bronchioles (900-1700 mm diameter) were analyzed and photomicrographs  400 were taken.…”
Section: Immunohistochemical Analysis Of Lung Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, when exposed to toxic factors, low levels of CC16 in the serum may be caused by a decrease in the number of Clara cells, changes in the permeability of the alveolar epithelium, and potentially by reduced expression of CC16 in airway epithelium. 5,6 In the PC group, the serum concentration of alveolomucin (40.89±3.49 U/mL, p<0.001 versus ETA, EAA), KL-6 (429.60±145.10 U/mL, p<0.002 versus EAA, p<0.005 versus ETA) and CC16 (7.541±0.87 ng/mL, p<0.02 versus EAA, p<0.005 versus ETA) was significantly lower than active occupational alveolitis. In remission, KL-6 and CC16 levels were not different from PC.…”
Section: Resultsmentioning
confidence: 98%
“…In patients with PAR, nasal fluid CC16 positively correlated with nasal nitric oxide (NO) levels, and the two negatively correlated with mast cell counts in the nasal mucosal lining, which points to the protective role of both CC16 and NO, as they inhibit cell chemotaxis in chronically inflamed nasal mucosa (12). In an experimental investigation, Roth et al (13) demonstrated that long-term exposure to perennial allergens caused most Clara cells to transform into large secretory goblet cells, which resulted in lower CC16 and higher mucus production in the bronchoalveolar mucosa. Studies with patients with PAR and CRSwNP demonstrated similar inhibition of CC16 nasal mucosa production by eosinophil inflammation (11,14).…”
Section: The Role Of Cc16 In Ar and Crsmentioning
confidence: 99%